The growing concern of Type 5 diabetes mellitus: A narrative review (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Type 5 diabetes mellitus (T5DM) is a developing form of diabetes linked to early childhood malnutrition, resulting from pancreatic underdevelopment due to nutritional deprivation during critical growth periods. This neglected health issue poses a challenge to achieving sustainable development goal 2: Zero Hunger, as food insecurity drives childhood stunting and poor maternal nutrition, contributing to T5DM, and ultimately jeopardising the targets of sustainable development goals 3: Good health and well-being. This narrative review explores T5DM in the context of global trends to guide nutritional policy and chronic disease prevention in low- and middle-income countries, where poverty and metabolic dysfunction intersect.Methods: A review of 47 articles was conducted, including original studies, reviews, case studies, and policy reports. A structured search of PubMed, Scopus, Google Scholar and grey literature identified relevant studies published between 2020 and 2026 that focused on T5DM, malnutrition-related diabetes mellitus, and early-life malnutrition.Results: Evidence indicates that T5DM is driven by impaired pancreatic β-cell development resulting from fetal and early childhood nutritional deprivation. Mechanisms include epigenetic modifications, reduced β-cell mass, and altered incretin responses. Epidemiological patterns show that T5DM disproportionately affects populations exposed to chronic undernutrition, with low- and middle-income countries representing a high-risk setting due to persistent childhood stunting, wasting, and maternal undernutrition. These nutritional deficits create a biological environment conducive to long-term insulin deficiency and metabolic dysfunction.Conclusion: T5DM represents an emerging metabolic consequence of early-life nutritional deprivation. Addressing this challenge requires multi-sectoral strategies that strengthen maternal and child nutrition, improve food security, and integrate malnutrition-related diabetes awareness into national public health policies, supporting sustainable growth toward the 2030 development agenda.